If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(6x + -5) + 4x + -6 = -1 Reorder the terms: -1(-5 + 6x) + 4x + -6 = -1 (-5 * -1 + 6x * -1) + 4x + -6 = -1 (5 + -6x) + 4x + -6 = -1 Reorder the terms: 5 + -6 + -6x + 4x = -1 Combine like terms: 5 + -6 = -1 -1 + -6x + 4x = -1 Combine like terms: -6x + 4x = -2x -1 + -2x = -1 Add '1' to each side of the equation. -1 + 1 + -2x = -1 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = -1 + 1 -2x = -1 + 1 Combine like terms: -1 + 1 = 0 -2x = 0 Solving -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-2'. x = 0 Simplifying x = 0
| 6x+8x-21=84-7x | | -0.8x-0.6+0.2x=12-4x | | -6x+2-x=2 | | -17-2x=-39 | | 6+x-1+2=7x-5-4x | | -15z=24z+36 | | Fx-gx=z | | 28x+27= | | 2((-8)-2)+8= | | 3x(2x+20)=4x-20 | | -9n+19=-8n-14 | | 6(9z-12)=9(5z+11) | | 2x+33?5x+6= | | 100x*10000=250x | | -6+4x+6x=-66 | | 4m-20=20-16m | | y=4x^3-.5x+2 | | 8c-120=240+5c | | 7x+8+4x=-80 | | x^4-20x^3+141x^2-406x+392*x-9=0 | | T(f+9)=40 | | 5y-7y=10 | | 6x-30=60-3x | | 9r-4=44+6r | | 5(2x+-7)-3(3x-10)+4= | | (D^3-D^2-4D-2)y=0 | | 46+16y=572 | | 4x-39=90 | | -17-20=-13x+80 | | 2x+3=9x+12-x | | 4x+2+6x=82 | | -5d+120=-6d-9 |